2021
DOI: 10.31580/apss.v8i1.1947
|View full text |Cite
|
Sign up to set email alerts
|

Travellers’ Satisfaction on the Applications of Artificial Intelligence in Malaysia’s Tourism and Hospitality Industry.

Abstract: Artificial intelligence (AI) is perceived as being able to transform tourism and hospitality industry’s operations into a greater efficiency and cost-effectiveness while offering travellers unique experiences. This study examines travellers’ satisfaction of AI applications, specifically through e-Hailing, e-Wallet, e-Gate and e-Visa in the tourism and hospitality industry in Malaysia. Quantitative research approach was adopted in the current study. Data was gathered from 200 respondents using self-administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Through research on artificial intelligence decision-making technology, it was found that artificial intelligence based on hyper-personalized products improved the conversion rate of advertisements and ultimately enhanced the traveler's experience [ 6 ]. Using quantitative research methods, Theam T S examined travelers' satisfaction with AI applications, especially through e-hailing, e-wallets, e-gates, and e-visas in Malaysia’ s tourism and hospitality industry [ 7 ]. Renjith S detailed the research on the evolution and characteristics and current limitations of travel recommendation systems, and also discussed the key algorithms used for the classification and recommendation process and the metrics that could be used to evaluate performance [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…Through research on artificial intelligence decision-making technology, it was found that artificial intelligence based on hyper-personalized products improved the conversion rate of advertisements and ultimately enhanced the traveler's experience [ 6 ]. Using quantitative research methods, Theam T S examined travelers' satisfaction with AI applications, especially through e-hailing, e-wallets, e-gates, and e-visas in Malaysia’ s tourism and hospitality industry [ 7 ]. Renjith S detailed the research on the evolution and characteristics and current limitations of travel recommendation systems, and also discussed the key algorithms used for the classification and recommendation process and the metrics that could be used to evaluate performance [ 8 ].…”
Section: Related Workmentioning
confidence: 99%